Pengaruh Problem Based Learning Terhadap Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 3 Malang - Yuliana Anggreini Budiman; Satrio Hadi Wijoyo; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Problem Based Learning is the learning model in which the focus of learning is in the real problem which had been given by the teacher in order to encourage the students to find out various information and knowledge as well as experience which can be useful to solve the problem by having group discussion. The aim of this research is to investigate whether PBL model can affect the students' learning outcomes. The focus of this research is the students' learning outcomes in cognitive and psychomotor aspect. The result of this study showed that there was no significant effect after implementing PBL model toward the students' learning outcomes in cognitive aspect. It is proven from the result of analyzing the data in which the significance value of the learning outcome in cognitive aspect is in the amount of 0.993, which is bigger than 0.05. Based on the criteria of success which had been set, it can be concluded that there was no significant effect in students' learning outcome in cognitive aspect after implementing PBL model. However, the result of this study showed that there was significant effect toward the students' learning outcomes in psychomotor aspect. It was proven from the result of analyzing the data in which the significance value of the learning outcome in psychomotor aspect is in the amount of 0.001, which is smaller than 0.05. Based on the criteria of success which had been set, it can be concluded that there was significant effect in students' learning outcome in psychomotor aspect after implementing PBL model.